2020
DOI: 10.1039/c9fd00124g
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent silicon nanoparticles for distinctive tracking of cellular targeting and trafficking

Abstract: We demonstrate tracking of silicon nanoparticles through intrinsic photoluminescence during the course of cellular targeting and uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“… 33 36 SiNPs with excellent biocompatibility have also been successfully applied in cell imaging and cell tracking. 37 , 38 The above reports indicated that SiNPs have excellent application potential in the field of analytical detection. So far, the fluorescence method based on SiNPs for VB 2 detection has not been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“… 33 36 SiNPs with excellent biocompatibility have also been successfully applied in cell imaging and cell tracking. 37 , 38 The above reports indicated that SiNPs have excellent application potential in the field of analytical detection. So far, the fluorescence method based on SiNPs for VB 2 detection has not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…As novel fluorescent probes, SiNPs have attracted the interest of researchers. In recent years, SiNPs have been used to detect metal ions such as Cu 2+ , Ag + , Fe 3+ , Hg 2+ , and Mn 2+ ; tetracycline antibiotic drugs such as tetracycline and oxytetracycline; , and essential nutrients for human body like vitamins, amino acids, glucose, and cholesterol. SiNPs with excellent biocompatibility have also been successfully applied in cell imaging and cell tracking. , The above reports indicated that SiNPs have excellent application potential in the field of analytical detection. So far, the fluorescence method based on SiNPs for VB 2 detection has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, fluorescent probes based on SiNPs were successfully used to detect heavy metal ions, , dopamine, amino acids, vitamins, nitro explosives, etc. Furthermore, SiNPs could also be used for pH sensing and bioimaging. , Nevertheless, the application of SiNPs in the detection of active ingredient of Chinese medicine is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, taking advantage of the low toxicity of silicon, fluorescent SiNPs have been extensively explored as prime candidates for biocompatible fluorescent nanostructures, holding tremendous promise for biosensing and bioimaging applications. Specifically, fluorescent SiNPs have been shown to be superbly suitable for use in long-term and real-time imaging, cellular targeting and trafficking, fluorescence ink, the detection and photodynamic treatment of bacterial infections, and cancer cell detection and therapy [ 25 , 26 , 27 , 28 , 29 , 30 ]. There have been advances in the understanding of the toxicity of SiNPs in both cell cultures and mammalian animal models, but these knowledges are still fragmented and sometimes inconsistent.…”
Section: Introductionmentioning
confidence: 99%